2021
DOI: 10.2174/1570159x19666201223154009
|View full text |Cite
|
Sign up to set email alerts
|

Recent Evidence in Epigenomics and Proteomics Biomarkers for Early and Minimally Invasive Diagnosis of Alzheimer’s and Parkinson’s Diseases

Abstract: Background: Alzheimer’s (AD) and Parkinson’s diseases (PD) show deposits of improperly folded modified proteins, so protein expression mechanisms are involved since early stages. Several studies evaluated epigenomics and proteomics profiles in these patients, with promising results. In general, they focused on early, specific, and minimally invasive biomarkers for diagnosis and prognosis of AD and PD. Objectives: This review aimed at summarizing results to find the most reliable evidence in the field. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 271 publications
(422 reference statements)
1
21
0
Order By: Relevance
“…Our study had different objectives, through the analysis of the transcriptome, but it certainly provides results that could be the basis of interesting future studies aimed at large-scale, numerical validation of what has been observed and, therefore, that could further confirm our findings. An emerging problem in the literature is the growing evidence in the field of proteomics in these pathologies, but studies are still few [82].…”
Section: Discussionmentioning
confidence: 99%
“…Our study had different objectives, through the analysis of the transcriptome, but it certainly provides results that could be the basis of interesting future studies aimed at large-scale, numerical validation of what has been observed and, therefore, that could further confirm our findings. An emerging problem in the literature is the growing evidence in the field of proteomics in these pathologies, but studies are still few [82].…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have shown that low levels of miRNAs miR-27a-3p ( 43 ) and high levels of miR-483-3p ( 44 ) can promote the development of AD. Moreover, miR-342-3p ( 45 ) and miR-103a-3p ( 46 ) affect the occurrence and subsequent stages of AD. The purpose of our study was to clarify the mechanisms underlying AD development by screening for miRNAs that affect AD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, several proteins were associated with synaptic structures, including downregulated (caskin-1, TMEM163 and REEP2) and upregulated (δ2-catenin, AHA-1, PHYHIPL and α-1-syntrophin) proteins, suggesting that hippocampal synaptic dysfunction plays a role in PD. However, minimally invasive samples (i.e., serum and plasma samples) are predominantly used to evaluate proteome profiles in PD, with the results highlighting the importance of coagulation, inflammation, and oxidative stress pathways (Mayo, Benito-León, Peña-Bautista, Baquero, & Cháfer-Pericás, 2021). In addition, in comparison with healthy participants, PD patients showed differences in the levels of some proteins, such as CRP, interleukins, necrosis factors, transferrin, glia fibrillary acidic protein (GFAP), neurofilament proteins, Rab35, ApoA1, and DJ-1.…”
Section: Parkinson's Diseasementioning
confidence: 99%